Prevalence and associated factors of intimate partner violence against pregnant women who attend antenatal care in Denmark and Spain: A digital screening approach - Rodrigo Fernández‐López; Karen Andreasen; Lea Ankerstjerne; Stella Martín‐de‐las‐Heras; Vibeke Rasch; Jesús L. Megías; Ditte S. Linde; Sabina de‐León‐de‐León; Berit Schei; Chunsen Wu; Alba Oviedo‐Gutiérrez; Antonella Ludmila Zapata‐Calvente (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Intimate partner violence against women is a global health issue. Exposure to intimate partner violence during pregnancy leads to health‐related problems for both the mother and the newborn. However, current knowledge on its occurrence varies widely and assessing the problem using standardized tools in different contexts is needed. This study aimed to estimate the prevalence and associated factors of IPV in pregnant women in Denmark and Spain through digital screening tools. Material and Methods A cross‐sectional design was used to systematically screen for intimate partner violence among pregnant women attending antenatal care by using standardized digital screening tools, Woman Abuse Screening Tool and Abuse Assessment Screen. Results A total of 17 220 pregnant women in Denmark and 2222 pregnant women in Spain were invited to participate. The response rate was high in both countries (77.3% and 92.5%, respectively). Overall, 6.9% (n = 913) and 13.7% (n = 282) screened positive in Denmark and Spain, respectively. Logistic regressions estimated crude and adjusted odds ratio with 95% confidence intervals of the relationship between sociodemographic variables and intimate partner violence. In both countries, being unmarried and lacking social support were risk factors of intimate partner violence. Additionally, in Denmark, pregnant women older than 40 years, unemployed or foreign, were at higher risk, while having higher educational levels was a protective factor. In Spain, not having a partner at the time of questionnaire completion and having at least one child prior to the current pregnancy were risk factors of intimate partner violence. Conclusions Prevalence results and found associated factors contribute to a more comprehensive understanding of the occurrence of intimate partner violence during pregnancy in Denmark and Spain, while highlighting the feasibility of digital systematic screening in antenatal settings.